The effect of dietary fish oil replacement by microalgae on the gilthead sea bream midgut bacterial microbiota - Katsoulis-Dimitriou, Stefanos; Nikouli, Eleni; Gkalogianni, Elli Zafeiria; Karapanagiotidis, Ioannis T.; Kormas, Konstantinos A. (Peer Community Journal, 2024)

(untitled)
It is well known that the gut microbiome and its interaction with the host influence several important factors for fish health such as nutrition and metabolism. Diet is one of the main factors influencing the composition of the gut microbiome in reared fish. Microalgae, due to their high fatty acid content, appear to be a promising alternative for replacing fish oil in aquafeed. Thus, the aim of this work was to evaluate the effects of dietary microalgae blends as fish oil replacers οn the midgut bacterial microbiota of the gilthead sea bream (Sparus aurata). The control diet (FO) contained only fish oil as a source of lipids, EPA and DHA fatty acids, while three experimental diets were used where fish oil was replaced at 67% by one of the following microalgae biomass blends: Microchloropsis gaditana and  Isochrysis sp. (Tisochrysis lutea) (MI), Phaeodactylum tricornutum and  Isochrysis sp. (PI) and Schizochytrium sp.  and P. tricornutum (SP). The midgut bacterial community composition of the experimental diets was altered compared to the control diet. There were 11 operational taxonomic units (OTUs) that were highly abundant in FO compared to the three experimental diets (FO, MI, SP) and two OTUs that were found in high abundance in both FO and the experimental diets in all comparisons (FO-MI, FO-PI, FO-SP). Most of the highly abundant OTUs in the experimental diets were unique to each experimental diet, with two OTUs being found in common between FO-MI and FO-PI. Additional evidence from the presumptive bacterial functional metabolic pathways suggested that the microalgae-based diets resulted in one over-expressed and one under-expressed pathway. The overexpressed pathway was related to the metabolism of fucose, a major constituent of the polysaccharide content of several microalgal species. Peptidoglycan biosynthesis was the under-expressed metabolic pathway. This suggests that a new gut microbiota profile was selected due to the microalgae inclusion in the provided diet. This study showed that, with the absence of mortality in fish, the gilthead sea bream gut microbiome can smoothly adapt its function according to the metabolic capacity of the dietary microalgae combinations that were used. The MI feed seems to promote several beneficial bacteria with potential probiotic abilities in the fish gut, belonging to the Pseudoalteromonas, Pseudomonas, Bacillus and Rhodopseudomonas genera.